Determining Professional Mobility Levels of Secondary School Teachers - Ismailova, G.; Mamanova, A.; Aypova, G.; Begaliyeva, N.; Konyrbayeva, S.; Sultanbek, M. (Determining professional mobility levels of secondary school teachers, International Journal of Cognitive Research in Science, Engineering and Education (IJCRSEE), 8(3), 39-45., 2020)
Education has a great share in the development of a country. Countries that invest in education are developing in all respects. There are many factors that affect education, but the most important of them is the teacher. Because other factors affecting education do not make sense without a teacher. The better the teachers are trained, the more appropriate the working conditions, the better the quality of education, and thus the establishment of a modern, peaceful country. This study aims to determine professional mobility levels of secondary school teachers. Mixed research method was used in the study. A total number of 146 teachers including 60 teachers in the control group and 86 in the experimental group participated in the study. Results confirmed the effectiveness of activities to update students’ pedagogical experiences as a necessary step in the development of professional pedagogical mobility. Results are discussed with relevant literature and recommendations for further research and practices are provided.
Keywords: Professional mobility, secondary school teachers, mixed research